The Linguistic and Legal Implications of ‘Waḍribūhunna’ in Sūra al-Nisāʾ (4:34) - Tahir-ul-Qadri, Prof Dr Muhammad (Al-Irfan, 2023)
This article presents a thorough examination of the word ‘ḍarb’ within the context of marital relations as depicted in verse 34 of Sura al-Nisaʾ. While traditionally translated as ‘strike them’, this study explores an alternative rendering as ‘turn them away’, as proposed in The Manifest Qur’an, aligning with Islamic principles of marital reconciliation and equitable treatment of women. The analysis encompasses various linguistic nuances of ‘ḍarb’ in classical Arabic, tracing its etymological roots and lexical meanings. Furthermore, it evaluates the chosen translation’s congruence with the Qur’ānic approach to resolving marital discord, incorporating insights from Prophetic teachings found in the Sunna regarding the physical ‘disciplining’ of women. Additionally, the abstract addresses potential misunderstandings arising from certain narratives about hitting, offering a nuanced understanding grounded in both linguistic and religious contexts. This comprehensive exploration sheds light on the intricate interplay between language, culture and religious interpretation within Islamic jurisprudence.